Oar_Finn: the genome assembly and annotation of an exceptionally fertile Finnsheep (Ovis aries) Ewe - Kantanen, Juha; Weldenegodguad, Melak; Pokharel, Kisun (BioMed Central, 2025)
Objectives Finnsheep, a highly prolific breed of sheep, has been globally exported for improving fertility traits of many sheep breeds. Published genomic studies of Finnsheep have been based on Texel and Rambouillet reference genomes, which may not capture its unique genetic features. Our main objective was to generate a high-quality Finnsheep genome assembly and its annotation that could serve as a breed-specific reference for studying fertility and adaptation in Finnsheep and other short-tailed northern European sheep breeds. Data description We generated a 2.53 Gb assembly using PacBio HiFi long-reads and Hi-C sequencing from a highly fertile Finnsheep ewe. The assembly, scaffolded with Hi-C data has a contig N50 of 35.5 Mb and scaffold N50 of 100.6 Mb. Gene annotation identified 42,533 genes spanning 46.5 Mb of coding region. BUSCO completeness for the assembly and annotation was 94.9% and 84.3%, respectively. This data, including raw reads, assembly, and annotations supports genomic studies of Finnsheep and other prolific breeds of sheep that are particularly adapted to northern European environments.
How to cite: Kantanen, J., Weldenegodguad, M. & Pokharel, K. Oar_Finn: the genome assembly and annotation of an exceptionally fertile Finnsheep (Ovis aries) Ewe. BMC Genom Data 26, 59 (2025). https://doi.org/10.1186/s12863-025-01354-x
Keywords: PacBio; fertile breed; genetic resources; finnsheep; assembly; annotation; BUSCO